Community-physician-based versus hospital-based antenatal care: A comparison of patient satisfaction - Mauwane R. Phaladi- Digamela (AOSIS, 2014)
Background: Strategies to meet the healthcare needs of pregnant women are made available throughout antenatal, intra-partum and post-natal periods. These strategies are aimed at reducing perinatal and maternal mortality amongst women who access and utilise healthcare at an early stage. Late visits with irregular antenatal attendance result in failure to adequately use antenatal interventions. Objectives: This study intended to compare and describe the level of patient satisfaction with antenatal care between two groups of women who received free antenatal care from community private physicians and public midwives. Methods: A quantitative comparative descriptive design with a Likert-scale measure was used. Sixty women, half from each group, participated in the study. Structured questionnaires with closed-ended response options were used to obtain data. Results: The midwives' group was less satisfied with antenatal care than the physicians' group, with the former citing long waiting times as contributing to their dissatisfaction with antenatal care. Conclusion: Addressing long waiting times improves satisfaction with antenatal care. Daily antenatal visits, rather than visits on a specific day, may reduce long waiting times as women's visits are spread over all clinic days. Satisfaction with antenatal care has implications for access to healthcare, resulting in positive pregnancy outcomes.